Reviewing the Pathogenic Potential of the Otitis-Associated Bacteria Alloiococcus otitidis and Turicella otitidis - Lappan, Rachael; Jamieson, Sarra E.; Peacock, Christopher S. (Frontiers in Cellular and Infection Microbiology, 2020)
Alloiococcus otitidis and Turicella otitidis are common bacteria of the human ear. They have frequently been isolated from the middle ear of children with otitis media (OM), though their potential role in this disease remains unclear and confounded due to their presence as commensal inhabitants of the external auditory canal. In this review, we summarise the current literature on these organisms with an emphasis on their role in OM. Much of the literature focuses on the presence and abundance of these organisms, and little work has been done to explore their activity in the middle ear. We find there is currently insufficient evidence available to determine whether these organisms are pathogens, commensals or contribute indirectly to the pathogenesis of OM. However, building on the knowledge currently available, we suggest future approaches aimed at providing stronger evidence to determine whether A. otitidis and T. otitidis are involved in the pathogenesis of OM. Such evidence will increase our understanding of the microbial risk factors contributing to OM and may lead to novel treatment approaches for severe and recurrent disease.